Shale gas and fracking : the science behind the controversy - Stephenson, Michael H. (Amsterdam, Netherlands ; Waltham, MA, USA : Elsevier Ltd., 2015)
Reviews and explains some of the key peer-reviewed, independent scientific studies related to shale gas and its production as well as the extraction of other fuel sources and the storage of waste products associated with them.
Shale Gas and Fracking: The Science Behind the Controversy explains the relevant geological principles before examining the peer-reviewed evidence and presenting it through a simple and compelling illustrated narrative. Each chapter focuses on a particular controversy, such contamination of well water with gas from fracking, and follows a similar format: starting with the principles; then detailing peer-reviewed case studies for earthquakes, radioactivity, and climate change; and concluding with a judgment of the general risks involved. Shale Gas and Fracking: The Science Behind the Controversy provides readers with the unbiased information they need to make informed decisions on the controversial issue of fracking.
The Fuss about Shale -- Shale, Shale Everywhere -- To Frack or Not to Frack? -- Gas in Our Water? -- Did the Earth Move? -- The Shale Gas Factory -- Shale Gas and Climate -- Keeping Watch -- The Science behind the Controversy.
Includes bibliographical references and index.
Print version record.
Keywords: Gas well drilling -- Environmental aspects; Hydraulic fracturing -- Environmental aspects; Shale gas industry -- Environmental aspects; TECHNOLOGY & ENGINEERING -- Mining; Gas well drilling -- Environmental aspects; Electronic books; Electronic book